A Review of Mutra pariksha in Unpublished Manuscript Atreyavirachita sarasamgraha: A Comparative Insights with AyurvedicLiterature - Vadhel, Manisha; Vyas, Hitesh A (International Research Journal of Ayurveda & Yoga, 2025)
Introduction: Mutra pariksha (urine investigation) is an essential diagnostic tool in Ayurveda, facilitating accurate diagnosis and holistic treatment. It is not mentioned directly in Brihattrayi (three major classical texts of Ayurveda) but its elements are dispersed under the Purvarupa (prodromal symptoms), Rupa (signs and symptoms), etc. Yogaratnakara included Mutra pariksha in eight types of Rogi pariksha (patient examination). The ‘Atreya virachita sarasamgraha,’ an unpublished manuscript attributed to Atreya, is composed in the Devanagari script and Sanskrit language. This manuscript has distinct description of Mutra pariksha. Aim: To review and compare the Mutra pariksha described in the unpublished manuscript namely Atreya virachita sarasamgraha for any novelty. Material and Method: For this study, eight manuscripts based on inclusion criteria were studied among 27 manuscripts obtained from various libraries. Observations & Results: The manuscript’s second chapter comprehensively explores urine collection and analysis, emphasizing factors such as Prakriti (temperament), Sama-nirama state, disease conditions, prognosis, treatment, and Tailabindu pariksha. This text elaborates on Mutra pariksha, emphasizing Varna (color), Sparsha (touch), Dhara (stream), and Vishesha Rupa (specific characteristics) for various disease conditions, with a methodology distinct from the Yogaratnakara. Conclusion: A comparative analysis reveals significant similarities between the Mutra pariksha described in the text and the Vangasena samhita.